Pengaruh Pendekatan CTL Melalui Metode Eksperimen Terhadap Hasil Belajar IPA Kelas V SDN 59 Bengkulu - Sukma Nerawati; Dalifa Dalifa; Syahril Yusuf (JURIDIKDAS, 2019)
The purpose of this study was to describe "The Effect of the Contextual Teaching and Learning Approach Through Experimental Methods on Water Recycling Materials on Student Learning Outcomes Cognitive, Affective, Psychomotor Aspects in Grade V Science Subjects of Elementary School Number 59 of Bengkuu City. This type of research is quantitative with the Experimental Quasy method with the design of The Matching Only Pretest-Posttest Control Group Design that was carried out in class V of Elementary School Number 59 of Bengkuu City The population in this study were grade V students of Elementary School Number 59 of Bengkuu City totaling 60 students.  The research sample was taken using Cluster Random Sampling technique so that the VA class was obtained, amounting to 31 students as the experimental class, class V B which amounted to 29 students as the control class. Class VA of Elementary School Number 59 of Bengkuu City as an instrument trial class. The research instruments were in the form of test sheets and observation sheets. Based on the hypothesis test t-test two independent samples, it was found that: there is the influence of cognitive, affective and psychomotor learning outcomes between students who take part in learning by applying the contextual teaching and learning approach through experimental methods with conventional approaches.